PENGARUH PENDEKATAN DEEP LEARNING BERBANTUAN GEOGEBRA TERHADAP PEMAHAMAN KONSEP SISWA PADA MATERI BANGUN DATAR - Gita Apriyanti; M. Maulana; Enjang Yusup Ali (Universitas Negeri Medan, 2026)
This study aims to identify the effect of using a GeoGebra-supported deep learning approach compared to conventional learning, as well as to analyze differences in conceptual understanding between the two groups of students regarding the properties of two-dimensional shapes in fifth-grade elementary school. The research method used was a quantitative experiment with a nonequivalent control group design and purposive sampling. The effect of learning in the experimental class was tested using a paired t-test, while in the control class, the Wilcoxon test was used because the data were not normally distributed. The results showed that both learning approaches had a significant effect on students’ conceptual understanding, with an effect size of 33.87% in the experimental class and 47.61% in the control class. The difference in the improvement in understanding between the two groups was analyzed using an independent samples t-test, which showed a significant difference between the two groups. Based on these results, it can be concluded that the GeoGebra-assisted deep learning approach is more effective in improving students’ conceptual understanding compared to conventional learning.